Convergences and divergences in sustainable entrepreneurship and social entrepreneurship research: A systematic review and research agenda - Bonfanti, Angelo; De Crescenzo, Veronica; Simeoni, Francesca; Loza Adaui, Cristian R. (Journal of Business Research, 2024)
Entrepreneurial ventures that explicitly address social and environmental issues have proliferated, together with diverse but strictly connected research streams and academic discussions around the phenomena of social entrepreneurship and sustainable entrepreneurship. However, while existing literature reviews address either social or sustainable entrepreneurship, studies systematizing the convergences and divergences of both sustainable and social entrepreneurship simultaneously in the academic literature are lacking. To fill this gap, the authors performed a systematic literature review covering the Scopus and Web of Science databases from 2001 to 2022. A total of 209 articles were reviewed, and thematic and lexical data analyses were conducted. As a result, convergences and divergences related to enablers, impact, business models, financial constraints, and fundraising instruments were identified. This article concludes by providing insights about knowledge gaps associated with the role of entrepreneurs, networks, impact measurement, business model innovation, and the capital structure of social and sustainable ventures.<br
Keywords: Sustainable entrepreneurshipSocial entrepreneurshipSystematic literature reviewABS journal ranking list